Oxford new syllabus primary Mathematics book 5 - Yee, Dr foong pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Book 5 is designed for primary school students, typically in their fifth year, to help them further develop their mathematical skills. This book builds on the concepts introduced in earlier books and introduces more advanced topics in line with the curriculum, preparing students for the transition to more complex mathematics.
Keywords: Mathematics : Textbook